2007
DOI: 10.1080/15569520701212373
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Barrier Creams Against Sulphur Mustard: (II)In VivoandIn VitroStudies using the Domestic White Pig

Abstract: Previous studies in our laboratory have demonstrated that barrier creams, comprising perfluorinated polymers, are effective against the chemical warfare agent sulphur mustard (SM) when evaluated using human skin in vitro. The purpose of this follow-up study was to further evaluate three candidate (perfluorinated) barrier creams against SM (vapour) using the domestic white pig. The severity and progression of the resulting skin lesions were quantified daily for three weeks post-exposure using biophysical measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…One must also take into account skin temperature, pH, the thickness of the layer of cream, the number of applications, drying time before exposure, time required for application, time in contact with the irritant, concentrations and quantities of the irritant agents, areas of the body studied (back, hands or forearms), subjects studied (gender and ethnicity), presence or absence of occlusion and the length of the study [4,28,41,53]. Human skin is also characterized by an interindividual variability [22].…”
Section: Discussionmentioning
confidence: 99%
“…One must also take into account skin temperature, pH, the thickness of the layer of cream, the number of applications, drying time before exposure, time required for application, time in contact with the irritant, concentrations and quantities of the irritant agents, areas of the body studied (back, hands or forearms), subjects studied (gender and ethnicity), presence or absence of occlusion and the length of the study [4,28,41,53]. Human skin is also characterized by an interindividual variability [22].…”
Section: Discussionmentioning
confidence: 99%
“…Skin diffusion cells systems are routinely used to measure the percutaneous absorption of chemicals of interest (or prevention of percutaneous absorption), are subject to guidelines regarding their use (OECD Guideline 428) and have been previously subject to international validation (Chilcott et al, 2005). Previous work has used diffusion cell methodology to elucidate the penetration characteristics of the CW agents HD and VX in the presence and absence of topical countermeasures (Chilcott et al, 2000(Chilcott et al, , 2001(Chilcott et al, , 2002(Chilcott et al, , 2007Dalton et al, 2006aDalton et al, , 2006bHattersley et al, 2008). Moreover, recent work has been carried out with VX regarding cross-species extrapolation to humans (Dalton et al, 2006a).…”
Section: Skin Surfacementioning
confidence: 99%
“…In vitro studies have shown that both the rate and the total amount of SM penetration are significantly enhanced through damaged skin (Lydon et al ., ), Thus, it is conceivable that the progression of SM injury could be more rapid if the skin were damaged. While a number of in vivo studies have evaluated decontamination of SM‐exposed undamaged skin (Wormser et al ., ; Chilcott et al ., ; Taysse et al ., , ), data on the decontamination of SM‐exposed damaged skin are limited to visual scoring of gross lesions and changes in leukocyte number (Gold et al ., ). This paucity of data poses a substantial problem in the establishment of best practice protocols for decontaminating individuals who have abraded skin or have sustained blast or similar injuries.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have shown that both the rate and the total amount of SM penetration are significantly enhanced through damaged skin (Lydon et al, 2017), Thus, it is conceivable that the progression of SM injury could be more rapid if the skin were damaged. While a number of in vivo studies have evaluated decontamination of SM-exposed undamaged skin (Wormser et al, 2002;Chilcott et al, 2007;Taysse et al, 2011Taysse et al, , 2007, data on the decontamination of SM-exposed damaged skin are limited to visual scoring of gross lesions and changes in leukocyte number (Gold et al, product suitable for halting bleeding and decontaminating wounds or abraded skin would be of significant clinical benefit. Previous studies have demonstrated that WoundStat ™ , a granular haemostat, has comparable efficacy to in-service military decontaminants (fuller's earth and M291) in the decontamination of both undamaged and damaged skin , Lydon et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation